1999
DOI: 10.1677/joe.0.1630229
|View full text |Cite
|
Sign up to set email alerts
|

Prolactin protects against diabetes induced by multiple low doses of streptozotocin in mice

Abstract: In earlier studies it has been shown that prolactin (PRL) is a stimulating factor for the immune system, and it has been suggested that PRL might antagonize immunosuppressive effects of glucocorticoids. PRL has been reported to affect the cytokine secretion pattern, by elevating cytokine gene expression in macrophages, after the onset of sepsis. It also promotes the antibody response in mice where it increases the production of interferon-(IFN-) and inhibits interleukin-1 (IL-1) production. Due to these proper… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
25
0

Year Published

2001
2001
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(27 citation statements)
references
References 31 publications
2
25
0
Order By: Relevance
“…This is in agreement with in vitro studies showing that growth hormone abrogates cytokine-induced apoptosis in INS-1 cells through activation of STAT5 (15). Moreover, protection against STZ-induced diabetes was also observed in mice with transgenic expression of placental lactogen in ␤-cells (5,6) or by injection of prolactin (46). The mechanism for the protective effect of STAT5 against ␤-cell destruction may involve members of the Bcl-2 family, as growth hormone stimulates the ␤-cell expression of Bcl-X L (15), which is a target gene of STAT5 involved in antiapoptosis (47).…”
Section: Discussionsupporting
confidence: 90%
“…This is in agreement with in vitro studies showing that growth hormone abrogates cytokine-induced apoptosis in INS-1 cells through activation of STAT5 (15). Moreover, protection against STZ-induced diabetes was also observed in mice with transgenic expression of placental lactogen in ␤-cells (5,6) or by injection of prolactin (46). The mechanism for the protective effect of STAT5 against ␤-cell destruction may involve members of the Bcl-2 family, as growth hormone stimulates the ␤-cell expression of Bcl-X L (15), which is a target gene of STAT5 involved in antiapoptosis (47).…”
Section: Discussionsupporting
confidence: 90%
“…Diabetes was induced in Balb/c mice by intraperitoneal (i.p.) injection of STZ (Sigma) at 40 mg/kg for 5 consecutive days, as reported previously [22]. Diabetes was monitored by measurement of blood glucose (BG) concentration from the tail vein using a blood glucose device (Roche Accu Check III, Roche, Basel, Switzerland).…”
Section: Streptozotocin (Stz) Induction Of Diabetesmentioning
confidence: 99%
“…Studies indicate that PRL may influence the Th1/Th2 balance and this may influence the development of autoimmune diseases [11]. In line with this, it was shown that administration of PRL could counteract hyperglycemia in mice treated with multiple low doses of streptozotocin (STZ) [12], which is a well characterized model of type 1 diabetes [13]. This could suggest that the influence of PRL on the immune system may convey a protective action against type 1 diabetes.…”
Section: Introductionmentioning
confidence: 80%